O ensino da matemática e a utilização do lúdico nos anos iniciais do ensino fundamental - Araripe, Paulo Roberto Esteves (2019)
One of the great problems in learning is Mathematics and to improve the understanding of the students has been proposed by the teachers the application of ludic activities. Given this scenario, the general objective of this study is to identify the main contributions of the use of play activities in the process of teaching mathematics to the children of the initial years of Elementary School. To this end, the following specific objectives were established: to explain the challenges of education; describe the innovations in the teaching of Mathematics; and, explain about the playful in the teaching of Mathematics. To reach this proposal, the methodology was based on a bibliographic, descriptive and exploratory research with secondary data with a qualitative approach, obtained from reading books, articles, other academic works and internet sites. Thus, with the result of the study it can be verified that the teachers of the initial years can make use of several tools to develop playful activities in the classroom in the initial years of elementary school. These results were based on the teachings of Albuquerque (2014), Freire (1996), Santos (2001) and Viana (2016). It is concluded with the study that in the process of teaching and mathematical learning is essential the interpersonal relationship between the students and between them and the teachers, since it facilitates the communication and daily practice of the study with play activities, and the teacher must have the necessary knowledge of these playful tools to be able to use in the classroom and facilitate the learning of Mathematics in the early years of Elementary School